(untitled) (Scientific journal of the Fergana State University, 2023)
The fauna of beetle-winged hololithous plants of the Fergana Valley is rich in species, it was found that there were 35 species belonging to 28 genera of 11 families. Of these, 28 species of beetles show trophic relationships with plants, and 7 species of beetles are entomophages. Among the identified species, 2 species were noted for the first time for the fauna of Uzbekistan. Also, the number of species recorded for the first time in the entomofauna of hololithous plants of the Fergana Valley is 5. Species identified for the first time in Uzbekistan, as well as on the territory of the Fergana Valley, are adventitious in nature, and their introduction is associated with the acclimatization of ornamental trees and shrubs in our region in recent decades.